Dynamic functional contribution of the water channel AQP5 to the water permeability of peripheral lens fiber cells - Petrova, Rosica S.; Webb, Kevin F.; Vaghefi, Ehsan; Walker, Kerry; Schey, Kevin L.; Donaldson, Paul J. (American Physiological Society, 2018)
Although the functionality of the lens water channels aquaporin 1 (AQP1; epithelium) and AQP0 (fiber cells) is well established, less is known about the role of AQP5 in the lens. Since in other tissues AQP5 functions as a regulated water channel with a water permeability (PH2O) some 20 times higher than AQP0, AQP5 could function to modulate PH2O in lens fiber cells. To test this possibility, a fluorescence dye dilution assay was used to calculate the relative PH2O of epithelial cells and fiber membrane vesicles isolated from either the mouse or rat lens, in the absence and presence of HgCl2, an inhibitor of AQP1 and AQP5. Immunolabeling of lens sections and fiber membrane vesicles from mouse and rat lenses revealed differences in the subcellular distributions of AQP5 in the outer cortex between species, with AQP5 being predominantly membranous in the mouse but predominantly cytoplasmic in the rat. In contrast, AQP0 labeling was always membranous in both species. This species-specific heterogeneity in AQP5 membrane localization was mirrored in measurements of PH2O, with only fiber membrane vesicles isolated from the mouse lens, exhibiting a significant Hg2+-sensitive contribution to PH2O. When rat lenses were first organ cultured, immunolabeling revealed an insertion of AQP5 into cortical fiber cells, and a significant increase in Hg2+-sensitive PH2O was detected in membrane vesicles. Our results show that AQP5 forms functional water channels in the rodent lens, and they suggest that dynamic membrane insertion of AQP5 may regulate water fluxes in the lens by modulating PH2O in the outer cortex.